The Behavior of the Citizens from Cluj-Napoca Regarding Advertising - Ioan LAZĂR (Transylvanian Review of Administrative Sciences, 2006)
This article strives to identify the Cluj- Napoca citizens’ attitude towards advertising. The analysis concludes, based on an empirical study, that the citizens of the third millennium from Cluj-Napoca have a positive attitude with regard to advertising.